Pengaruh Pemberian Jus Tomat terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil: The Effect of Tomato Juice Administration on the Increase of Hemoglobin Levels in Pregnant Women - Salsabila, Nanda Lutfia; Agustina, Indah Fitri; Irayani, Fahrul (Chakra Brahmanda Lentera Institute, 2026)
Iron-deficiency anemia during pregnancy remains a major public health concern because it increases the risk of adverse maternal and neonatal outcomes. Although iron supplementation is routinely recommended, its effectiveness may be limited by suboptimal iron absorption. Tomato juice, a natural source of vitamin C, has the potential to enhance non-heme iron absorption and improve hemoglobin synthesis. This study aimed to evaluate the effect of tomato juice combined with iron supplementation on hemoglobin levels among pregnant women with anemia. A quasi-experimental study with a pretest-posttest non-equivalent control group design was conducted among 28 anemic pregnant women in the second and third trimesters in Penengahan Village, South Lampung, Indonesia. Participants were allocated into an intervention group (iron supplementation plus 250 mL tomato juice daily for 14 days; n = 14) and a control group (iron supplementation only; n = 14). Hemoglobin levels were measured before and after the intervention using a standardized portable hemoglobin analyzer. Within-group and between-group differences were analyzed using paired and independent t-tests with a significance level of p < 0.05. Both groups demonstrated increased hemoglobin levels after the intervention. However, the intervention group showed a greater mean increase than the control group (1.17 vs. 0.71 g/dL). The improvement in the intervention group was statistically significant (p < 0.001), indicating that tomato juice enhanced the effect of iron supplementation on hemoglobin improvement. Daily consumption of tomato juice as an adjunct to iron supplementation was more effective than iron supplementation alone in increasing hemoglobin levels among pregnant women with anemia. Incorporating vitamin C-rich foods into antenatal nutritional programs may improve the effectiveness of anemia management during pregnancy.